(3GdJHUQIs - (3CHh GdMSf Ydj Hf eMeO GdQHYi GddNeis; (3YHO GdQMef Hf GdbGSe Hf NGdO Hf LfGOI GdYJbqj GdeGdcj GdeUQj, CHh YHO Gddg, hjYQa HGHf GdbGSe,J (B191 (3g` s
(3ChdgG (B:s
(3cJGH GdfPhQ HGH ai hLhH GdfPQh eG jLhR Refg s
(3BNQgG (B:s
(3ef cJGH GdfcGM GdChd (B: (3hYdi gPG dh COYi GdRhL Cf HPdc GdehVY HQUkG hCfcQJ jaJb GdKhH Yfg hjfXQ Edjg GdQLGd s
(3GdfSNI HgG MhGTs
(3HgPG GdLRA HjGV ai HYV GdUaMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B681s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: 518s
Keywords: (3Gdabg GdeGdcjs